Answer:[7,2]
Step-by-step explanation:
ANSWER

EXPLANATION
We want to evaluate

Use indices to rewrite the expression as:

We know that

So we rewrite the expression to obtain;

This gives us;

This simplifies to


Answer:
3 = 3 (infinitely many solutions)
Step-by-step explanation:
Answer:
y > -x + 3
Step-by-step explanation:
find the slope and y-intercept so you can create a linear equation:
y = mx + b ; m = slope and b = y-intercept
slope (m) = (3-0) / (0-3)
m = 3/-3 or -1
we can see the y-intercept by looking at the graph, it is 3
y > -x + 3
Answer:
x= 3 hope it helps thanks